To study the effect of glycemic control and duration of disease on pulmonary function tests and diffusion capacity in type 2 diabetes mellitus - Singh, Jitendra; Gupta, Kamlesh K.; Himanshu, D.; Dinkar, Anju; Atam, Virendra; Kant, Surya (International Journal of Research in Medical Sciences, 2017)
Background:Type 2 diabetes mellitus is known to cause serious progressive macro and micro vascular complications leading to end organ damage like retinopathy, nephropathy and neuropathy. Pulmonary complications due to collagen and elastin changes as well as microangiopathy has also been demonstrated in type 2 diabetes mellitus but prevalence in most of population is unknown and its possible correlation with duration of disease and degree of glycemic control is not studied more in our population. Aims and objectives: To compare Pulmonary Function Tests (PFT) in type 2 diabetes mellitus with control group and to evaluate possible correlation of PFT with status of sugar control and duration of disease. Methods:Consecutively consenting 120 subjects who satisfied the inclusion criteria were recruited over one year duration. These 120 subjects are categorised into two i.e. healthy volunteers recruited as controls (n=60) and type 2 diabetic patients (n=60). Results:Both group compared and studied with each other. Diabetic patients showed a significant reduction in Forced Expiratory Volume in one second (FEV1), Forced Vital Capacity (FVC) and pulmonary diffusion capacity for carbon monoxide (DLCO) relative to their matched controls and these values were further reduced in diabetic patients with uncontrolled glycemic status. Conclusion:Our study concluded that lung functions in type2 diabetes mellitus are impaired with restrictive pattern of respiratory abnormality. Duration of diabetes did not influence on pulmonary function and diffusion capacity.